Satellite-based regional scale climate data extractor for CWANA - Gafurov, Zafar (International Water Management Institute, 2023)
This web-app has been developed to ease the weather data acquisition process. This web-app allows the user to extract long-term monthly scale temperature and precipitation data for selected countries in the CWANA region. Users are required to indicate the country of interest and the desired time period. Consequently, the web-app presents annual weather information and time-series precipitation and temperature data as well as meteorological drought indices such as Standard Precipitation Index (SPI) and Standard Temperature Index (STI). Additionally, the platform allows users to generate spatial maps for weather parameters and to export data in the form of maps, tables and figures. This web-app automatically retrieves up-to-date weather data from the ERA5-Land archive. In order to extract the regional scale climate data, please indicate the area of interest by selecting an area from the bar. The dynamics of climate parameters over time will be demonstrated in the graph and map view. By clicking the button in the corner of the graph, the table form and picture form of the data can be obtained.